Sevoflurane Induced Diffuse Alveolar Hemorrhage in a young patient. (2017) - Austin, Adam; Modi, Aakash; Judson, Marc A.; Chopra, Amit
Abstract: We report a very rare case of Sevoflurane Induced Diffuse Alveolar Hemorrhage in a previously healthy young adult in the post-operative period following general anesthesia. Diffuse alveolar hemorrhage (DAH) associated with inhalation injury from halogenated gases is a unique entity in the literature that practicing clinicians should be cognizant of and considered in post-operative cases of acute respiratory distress whereby other etiologies have been excluded.